Long-term trends in ozone in baseline and European regionally-polluted air at Mace Head, Ireland over a 30-year period. (April 2018) - Derwent, Richard G.; Manning, Alistair J.; Simmonds, Peter G.; Spain, T. Gerard; O'Doherty, Simon
Abstract: Observations of surface ozone, O3, have been made at the Mace Head Atmospheric Research Station on the North Atlantic Ocean coastline of Ireland over a 30-year period from April 1987 through to April 2017. Using meteorological analyses and a sophisticated Lagrangian dispersion model, the hourly observations have been sorted by air mass histories to separate out the observations for northern hemisphere mid-latitude baseline air masses. Monthly average baseline levels showed a pronounced seasonal cycle with spring maxima and summer minima. Baseline levels have shown an increase during the 1980s and 1990s which has been stronger in the winter and spring and weaker in the summer. The rate of this increase has slowed to the extent that baseline levels have been relatively constant through the 2000s and started to decline in 2010s. The unsorted O3 data has shown different long-term trends from the baseline data because of the influence of European regional NOx and VOC emissions which have reduced wintertime O3 levels below the baseline levels and enhanced summertime O3 levels above them. Episodic peak O3 levels have declined steadily during the study period but 50 ppb 1 h exceedances are likely to continue for the foreseeable future. Highlights: 30 years of ozone observations for Mace Head, Ireland are presented. The importance of sorting the observations by air mass is stressed. Northern hemisphere baseline ozone levels have increased, levelled off and begun to decline.